2017
DOI: 10.1371/journal.pone.0181754
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex and trauma impact on the rupture site of the ulnar collateral ligament of the thumb

Abstract: Purpose and hypothesisAlthough sex- and gender-specific analyses have been gaining more attention during the last years they have rarely been performed in orthopaedic literature. The primary purpose of this study was to investigate whether for injuries of the UCL the specific location of the rupture is influenced by sex. A secondary study question addressed the sex-independent effect of trauma intensity on the rupture site of the UCL.MethodsThis study is a retrospective analysis of all patients with either a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
4
0
2
Order By: Relevance
“…The above findings are in agreement with those published in smaller surgical case series dating from Stener’s original publication to the only other large surgical series published in 2017 by Boesmueller et al 26 in Austria. Table reviews the values seen in 15 studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The above findings are in agreement with those published in smaller surgical case series dating from Stener’s original publication to the only other large surgical series published in 2017 by Boesmueller et al 26 in Austria. Table reviews the values seen in 15 studies.…”
Section: Discussionsupporting
confidence: 91%
“…Table reviews the values seen in 15 studies. 2 , 4 , 16 , 17 , 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Across nearly 60 years of published data, the UCL has been shown to predominantly tear distally at the proximal phalanx insertion, and the RCL has a more heterogenous tear location, with tears occurring frequently at both the proximal metacarpal origins and distally at the phalangeal insertion.…”
Section: Discussionmentioning
confidence: 99%
“…No estudo feito por Chuter et al 22 avaliaram retrospectivamente 127 pacientes submetidos a tratamento cirúrgico de lesão do LCU, observando que 62% eram do sexo masculino. Boesmueller et al 23 . estudaram a influência do sexo no sítio de lesão e intensidade do trauma nas lesões do LCU.…”
Section: Discussionunclassified
“…Outro mecanismo importante em nosso estudo foi queda de moto (19,9%). No estudo de Boesmuller et al 23 o mecanismo de trauma mais comum foi relacionado a esportes (51%), principalmente esquiagem. Os autores atribuiram este dado ao fato de o estudo ter sido realizado na Austria, país procurado com frequência para prática deste esporte.…”
Section: Discussionunclassified
“…In a study looking at the effect of sex and trauma intensity in thumb UCL injuries, it was found that proximal tears were more often associated with low-velocity injury, as in our case, whereas high-velocity injury was associated more often with distal tears. 9 It is possible that proximal injury of the UCL is favored by the way a deploying airbag strikes the thumb in a low-velocity motor vehicle crash. High-velocity motor vehicle crashes may more likely result in the thumbs being injured by the steering wheel or other parts of the car interior, leading to midsubstance or distal UCL injuries.…”
Section: Discussionmentioning
confidence: 99%